ANALISIS PERTIMBANGAN MAJELIS HAKIM AGUNG MENOLAK PERMOHONAN KASASI DALAM KASUS SENGKETA MEREK - Purnama, Aditya Putra; Chumbradika , Chitto; Wahyono, Wahyono (CV. Era Digital Nusantara, 2023)
Business actors must be aware of protecting trademarks by registering them with the Director General of Intellectual Property, Ministry of Law and Human Rights. The goal is for business owners to use their brand exclusively without plagiarism from other business actors who want to commercialize it. This study aims to analyze the considerations of the Supreme Court of Justice in rejecting an appeal for cassation in one of the brand dispute cases involving a public figure, namely Ruben Onsu and his former partner, namely PT. Geprek Chicken Benny Sujono. Research is included in normative juridical research, which uses primary legal materials. Data collection techniques were carried out through a literature study using qualitative data analysis methods. The results of the study show that based on Article 21 of the MIG Law it is explained that a trademark application will be rejected if the mark has similarities in substance or in whole with a registered mark belonging to another party or has been applied for beforehand by another party. As for the case of a trademark dispute that occurred as a case study, it can be concluded that based on the Supreme Court Decision Number 575 K/Pdt.Sus-HKI/2020, Ruben Onsu's lawsuit against the cancellation of the